PENERAPAN UNSUR MENS REA DALAM TINDAK PIDANA KORUPSI BERBASIS KEBIJAKAN PUBLIK: STUDI KASUS TOM LEMBONG - Usman Saputra; Edi Saputra Hasibuan; Marlina Samosir (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the evidence for the mens rea element of evil in corruption stemming from public policymaking, focusing on the alleged sugar import corruption case involving Tom Lembong. The primary issue in this case is the blurred line between policy discretion and corruption. Using normative juridical research methods and a case study approach, this study examines whether violations of administrative procedures automatically represent criminal mens rea (evil intent). The results show that in policy-based corruption, mens rea cannot be simply equated with administrative errors. Evidence of fraudulent intent, as defined by Article 2 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, is required, with the intention to enrich oneself, others, or corporations for illegitimate economic gain or to the detriment of the state. Law enforcement that relies solely on state losses without proving personal motives or kickbacks risks the criminalization of policies, which could stifle bureaucratic innovation in Indonesia.